(untitled) (Research Announcements "Heritage BG", 2025)
The article aims to reveal the socio-economic benefits of an approach to the creation and socialization of the historic complex Tsari Mali grad in the village of Belchin. The data were obtained from interviews and questionnaires among local businesses and visitors to the complex. The results confirm the desired economic and social benefits of the chosen approach to heritage in view of local development. The limitations of the study relate to the small number of interviewed businesses and visitors. Nevertheless, the article contributes to a better understanding of how a cultural heritage that is not of global or national importance can become a resource for local development. References: Alivizatou 2012: Alivizatou, Marilena. Debating Heritage Authenticity: Kastom and Development at the Vanuatu Cultural Centre. International Journal of Heritage Studies, Vol. 18, No. 2, 24-143. Ashworth 2011: Ashworth, Gregory. Preservation, Conservation and Heritage: Approaches to the Past in the Present through the Built Environment. Asian Anthropology, Vol. 10, Issue 1, 1-18. Ashworth 2008: Ashworth, Gregory. How do Tourists Consume Heritage Places? In: Cultural Heritage and Tourism. Potential, Impact, Partnership and Governance. A book on cultural heritage and tourism to inspire policy makers and practitioners at all levels, ed. by Lehtimäki, M., Proceedings of the III Baltic Sea Region Cultural Heritage Forum, Vilnius, 25-27 September 2007. Vilnius, 52-58. Baarveld et al. 2013: Baarveld, Marlijn, Smit, Marnix and Dewulf, Geert. Planning and Commitment in Cultural Heritage Projects. Journal of Cultural Heritage Management and Sustainable Development, Vol. 3, №. 2, 163-174. Cartmell et al. 2019: Cartmell, Lynn, Herndon, Tonia, Moffatt, Thomas and Lampe, Katy Mike Smaistrla. The Heritage Leadership Process: Exploring Meaning Making and Social Emotional Competencies in Heritage Interpretation and Education for Sustainability. Dissertations, 879, available at: https://irl.umsl.edu/ dissertation/879 (accessed 10 December 2020). De la Torre 2013: De la Torre, Marta. Values and Heritage Conservation. Heritage & Society, Vol. 60, No. 2, 155-166. Dümcke and Gnedovsky 2013: Dümcke, Cornelia and Gnedovsky, Mikhail. The Social and Economic Value of Cultural Heritage: literature review. EENC Paper, available at: https://www.interarts.net/descargas/interarts_2557.pdf (accessed 12 December 2020). Lazrak et al. 2014: Lazrak, Faroek, Nijkamp, Peter, Rietveld, Piet and Rouwendal, Jan. The Market Value of Cultural Heritage in Urban Areas: An Application of Spatial Hedonic Pricing. Journal of Geographical Systems, Vol. 16, 89-114. Lwoga 2018: Lwoga, Noel Biseko. Dilemma of Local Socio-economic Perspectives in Management of Historic Ruins in Kilwa Kisiwani World Heritage Site, Tanzania. International Journal of Heritage Studies, Vol. 24, № 10, 1019-1037. Mason 2008: Mason, Randll. Be Interested and Beware: Joining Economic Valuation and Heritage Conservation. International Journal of Heritage Studies, Vol. 14, Issue 4, 303-318. Nypan 2008: Nypan, Terje. The Economics of Built Heritage. In: Cultural Heritage and Tourism. Potential, Impact, Partnership and Governance. A book on cultural heritage and tourism to inspire policy makers and practitioners at all levels, ed. by M. Lehtimäki. Proceedings of the III Baltic Sea Region Cultural Heritage Forum, Vilnius, 25-27 September 2007. Vilnius, 59-61. Snowball 2008: Snowball, Jeanette D. Measuring the Value of Culture. Springer-Verlag Berlin Heidelberg, doi:10.1007/978-3-540-74360-6. Tamma 2010: Tamma, Michele. Prodotti culturali e territori: l’immateriale che ‘vive’ nella materialità. Cultura, arte e management: frontiere e connessioni. Atti del Convegno annuale di Sinergie, Università degli Studi di Trento, Sinergie, № 82, 27-46. UNWTO 2018: UNWTO. European Union Tourism Trends, available at: https://www.e-unwto.org/doi/pdf/10. 18111/9789284419470 (accessed 18 December 22020). Vakhitova 2015: Vakhitova, Tatiana Vadimovna. Rethinking Conservation: Managing Cultural Heritage as an Inhabited Cultural Landscape. Built Environment Project and Asset Management, Vol. 5, Issue 2, 217-228. Valchev 2018: Valchev, Georgi. Heritage ‘Renovation’ or Who and What Makes us Heirs. Seminar BG, special issue, available at: https://www.seminar-bg.eu/spisanie-seminar-bg/special-issue-4/item/540-heritage-%E2%80%9Crenovation%E2%80%9D-or-who-and-what-makes-us-heirs.html, (accessed 12 December 2020).